Marketing strategy for the creative and cultural industries - Kolb, Bonita M. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Developing and executing marketing strategies is a vital aspect of any business and few books currently cover this with relation to creative industries. This textbook provides students and managers in the creative industries with a solid grounding in how to maximize the impact of their marketing efforts across a range of business types in the creative and cultural industries The author, an experienced cultural marketing educator, provides sector-contextual understanding to illuminate the field by: taking a strategic approach to developing marketing plans bringing together strategic planning, market research, goal setting, and marketing theory and practice explaining how content marketing on social media encourages a relationship with consumers so that they co-promote the creative product With a range of learning exercises and real-life examples throughout, this text shows students how to create successful marketing plans for their creative businesses. This refreshed edition is a valuable resource for students and tutors of creative, cultural and arts marketing worldwide"--
OCLC-licensed vendor bibliographic record.
Keywords: Arts -- Marketing; Performing arts -- Marketing; Cultural industries -- Management; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / Industries / Service Industries